Pengaruh daya tarik wisata terhadap kepuasan wisatawan: studi kasus di Obyek Wisata Pemandian Air Panas Tempuran di Kabupaten Magelang - Arvina Aizil Fitroh; Johan Subarkah (PANUNTUN (Jurnal Budaya, Pariwisata, dan Ekonomi Kreatif), 2024)
This study examines how tourist attractions and facilities affect visitor satisfaction at Tempuran Hot Spring in Magelang Regency. Using a quantitative method with surveys, it evaluates two independent variables—attractions (X1) and facilities (X2)—and one dependent variable, visitor satisfaction (Y). Data from 99 respondents were analyzed using multiple linear regression via SPSS. Results show that attractions and facilities significantly influence visitor satisfaction. The findings provide insights for tourism managers to enhance attractions and facilities to improve visitor satisfaction at Tempuran Hot Springs.